2013
DOI: 10.3390/plants2040650
|View full text |Cite
|
Sign up to set email alerts
|

Calcium: The Missing Link in Auxin Action

Abstract: Due to their sessile lifestyles, plants need to deal with the limitations and stresses imposed by the changing environment. Plants cope with these by a remarkable developmental flexibility, which is embedded in their strategy to survive. Plants can adjust their size, shape and number of organs, bend according to gravity and light, and regenerate tissues that were damaged, utilizing a coordinating, intercellular signal, the plant hormone, auxin. Another versatile signal is the cation, Ca2+, which is a crucial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 224 publications
(294 reference statements)
0
67
0
Order By: Relevance
“…Stimulation of cytosolic Ca 2+ transients by auxin has been reported recently (Monshausen et al, 2011), and critical roles in mediating auxin responses have been suggested for intracellular Ca 2+ (Vanneste and Friml, 2013). Therefore, it is interesting to note that the mitochondrial matrix response to NAA was far more pronounced than that of the cytosol when measured in the root tip, a hot spot of auxin regulation (Figures 6 and 7).…”
Section: Toward An Understanding Of Subcellular Ca 2+ Dynamicsmentioning
confidence: 61%
“…Stimulation of cytosolic Ca 2+ transients by auxin has been reported recently (Monshausen et al, 2011), and critical roles in mediating auxin responses have been suggested for intracellular Ca 2+ (Vanneste and Friml, 2013). Therefore, it is interesting to note that the mitochondrial matrix response to NAA was far more pronounced than that of the cytosol when measured in the root tip, a hot spot of auxin regulation (Figures 6 and 7).…”
Section: Toward An Understanding Of Subcellular Ca 2+ Dynamicsmentioning
confidence: 61%
“…Numerous studies have suggested that Ca 2+ is involved in auxin signaling or responses (reviewed in Vanneste and Friml, 2013). Auxin induces a rapid and transient increase of cytosolic Ca 2+ concentration in various plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The processes from the [Ca 2+ ] c -increase to the gravitropic response, which are highly likely auxin dependent, 54 are also not identified yet, and left for future studies.…”
Section: Future Perspectivementioning
confidence: 99%